MODEL KOPERASI ISLAM DARI BEBERAPA NEGARA MUSLIM DAN NON MUSLIM - Amalia, Hani Khairo; Hidayat, Rofik (Universitas Negeri Surabaya, 2025)
This study explores the Islamic cooperative model, which is gaining increasing attention in the global economy, particularly among member countries of the Organization of Islamic Cooperation (OIC). Islamic economic principles, which emphasize social values, justice, and community empowerment, face challenges such as low human resource quality, limited capital, inadequate managerial capabilities, and low member awareness. With the rapid growth of cooperatives in various countries, new challenges and opportunities have emerged in developing cooperative models that align with Islamic economic principles while integrating local values and culture. This study aims to explore and analyze successful cooperative models implemented in several countries and investigate strategies and innovations for the sustainable and inclusive development of Islamic cooperatives. Using bibliometric and content analysis, this research finds that several Muslim and non-Muslim countries have developed innovative Islamic cooperative models. Integration with fintech can enhance efficiency and financial inclusion. Islamic cooperatives have demonstrated positive impacts on the economic and social welfare of communities. Recommendations include fostering innovation, promoting international collaboration, providing government policy support, and enhancing education and promotion to improve understanding and acceptance of Islamic cooperatives. Future research is suggested to conduct comparative studies, explore technology integration, and assess long-term impacts to expand the understanding of Islamic cooperative models and their potential.